The method of Sherborne Developmental Movement as a Means for the Development of Emotional Skills of Prepubertal Children - Mousouraki, Μαρία; Kouli, Όλγα; Michalopoulou, Μαρία; Kambas, Αντώνης; Goudas, Μάριος (Inquiries in Physical Education and Sport, 2018)
The purpose of this study was to investigate if the application of Sherborne Developmental Movement (SDM) can have a positive influence on the development of prepubertal children’s (10-12 years old) emotional skills. 126 students from two elementary schools in Attica attending 5th and 6th grade participated in this research. Sixty-four of them were the experimental group who participated in the SDM method and 62 of them were the control group who regularly participated only in scheduled Physical Education lessons. The assessment of the participants’ emotional skills (self-control, emotion management, and empathy) was based on the self-report scale of Emotional Competence from the Psychosocial Adjustment Test for 10-12 years old students (Chatzichristou, Polychroni, Bezevengis & Milonas, 2008). Analyzing the data, we can conclude, that the girls of the experimental group of both grades showed significant improvements on their «emotion regulation» emotional skill and the girls of 5th grade of the experimental group on the «self-control» emotional skill. Therefore, it seems, that the application of the SDM method in the school curriculum can improve the emotional skills of 5th and 6th grade girls, suggesting thus the importance of its contents for the emotional development of prepubertal children.